A novel combination of multiple primary carcinomas: Urinary bladder transitional cell carcinoma, prostate adenocarcinoma and small cell lung carcinoma- report of a case and review of the literature - Giannikaki Elpida; Datseris George; Dambaki Konstantina I; Koutsopoulos Anastassios V; Froudarakis Marios; Stathopoulos Efstathios (World Journal of Surgical Oncology, 2005)
Abstract Background The incidence of multiple primary malignant neoplasms increases with age and they are encountered more frequently nowadays than before, the phenomenon is still considered to be rare. Case presentation We report a case of a man in whom urinary bladder transitional cell carcinoma, metachronous prostate adenocarcinoma and small cell lung carcinoma were diagnosed within an eighteen-month period. The only known predisposing factor was that he was heavy smoker (90–100 packets per year). The literature on the phenomenon of multiple primary malignancies in a single patient is reviewed and the data is summarized. Conclusion It is important for the clinicians to keep in mind the possibility of a metachronous (successive) or a synchronous (simultaneous) malignancy in a cancer patient. It is worthy mentioning this case because clustering of three primary malignancies (synchronous and metachronous) is of rare occurrence in a single patient, and, to our knowledge, this is the first report this combination of three carcinomas appearing in the same patient.